Graphene e-tattoos for unobstructive ambulatory electrodermal activity sensing on the palm enabled by heterogeneous serpentine ribbons - Hongwoo Jang; Kaan Sel; Eunbin Kim; Sangjun Kim; Xiangxing Yang; Seungmin Kang; Kyoung-Ho Ha; Rebecca Wang; Yifan Rao; Roozbeh Jafari; Nanshu Lu (Nature Communications, 2022)
Designing efficient sensing devices for ambulatory use remains a challenge. Here, the authors demonstrate heterogeneous serpentine ribbons enable a stretchable and robust interface between sub-micron thin graphene e-tattoos and thick and rigid printed circuit boards, which allows ambulatory electrodermal activity monitoring on the palm.